Determinants of change in code status among patients with cardiopulmonary arrest admitted to the intensive care unit. (December 2022) - Ploch, Michelle; Ahmed, Talha; Reyes, Stephan; Irizarry-Caro, Jorge A.; Fossas-Espinosa, Jose E.; Shoar, Saeed; Amatullah, Atia; Jogimahanti, Arjun; Antonioli, Matthew; Iliescu, Cesar A.; Balan, Prakash; Naeini, Payam Safavi; et al.
Abstract: Background: Patients with cardiopulmonary arrest often have a poor prognosis, prompting discussion with families about code status. The impact of socioeconomic factors, demographics, medical comorbidities and medical interventions on code status changes is not well understood. Methods: This retrospective study included adult patients presenting with cardiac arrest to the intensive care unit of a hospital group between 5/1/2010–5/1/2020. We extracted chart data on socioeconomic factors, demographics, and medical comorbidities. Results: We identified 1, 254 patients, of which 57.5% were males. Age was different across the groups with (61.2 ± 15.5 years) and without (61.2 ± 15.5 years) code status change (p= <0.0001). Code status was changed in 583 patients (46.5%). Among patients with code status change, the highest prevalence was White patients (34.8%), followed by African Americans (30.9%), and Hispanics (25.4%). Compared to patients who did not have a code status change, those with a change in code status were older (66.7 ± 14.8 years vs 61.2 ± 15.5 years). They were also more likely to receive vasopressor/inotropic support (74.6% vs 58.5%), and broad-spectrum antibiotics (70.3% vs 57.7%). Insurance status, ethnicity, religion, education, and salary did not lead to statistically significant changes in code status. Conclusions: In patients with cardiopulmonary arrest, code status change was more likely to be influenced by the presence of medical comorbidities and medical interventions during hospitalization rather than by socioeconomic factors.